Two different small size testing technique for the creep residual life evaluation of an equiaxed Ni-based superalloy for GT blade and vane application. (3rd March 2016) - Vacchieri, E.; Holdsworth, S.R.; Poggio, E.; Parodi, S.; Villari, P.
Abstract : Two miniaturised creep testing techniques have been applied to a polycrystalline Ni-based superalloy employed for gas turbine blades and vanes. The test campaign was conducted on as-delivered material to assess both testing techniques and evaluate their effectiveness in determining creep residual life and creep residual properties of operated material. The first technique involved small size uniaxial creep testing, conducted on samples with a diameter lower than 3 mm. The diameter effect was deeply studied and a calibration was done to correlate results from standard creep test pieces with those from small diameter samples. The second technique involved the small punch creep test, and the assessment on virgin material enabled determination of the correlation factor, k sp, to compare small punch test results with uniaxial creep tests. All the collected results were related to the coarse grain macrostructure that characterises this class of alloys and that increases the scatter of the collected experimental results.